Matrix metalloproteinases gene variants and dental caries in Czech children - Borilova Linhartova, Petra; Deissova, Tereza; Kukletova, Martina; Izakovicova Holla, Lydie (BMC oral health, 2020)
BACKGROUND: Matrix metalloproteinases (MMPs) play an important role in tooth formation and the mineralization of dental tissue. The aim of the study was to analyse Czech children with primary/permanent dentition polymorphisms in those genes encoding MMP2, MMP3, MMP9, MMP13, MMP16, and MMP20, which had been previously associated with dental caries in other populations. METHODS: In total, 782 Czech children were included in this case-control study. DNA samples were taken from 474 subjects with dental caries (with decayed/missing/filled teeth, DMFT ≥ 1) and 155 caries free children (DMFT = 0) aged 13-15 years, as well as 101 preschool children with early childhood caries (ECC, dmft ≥ 1) and 52 caries free children (dmft = 0), were analyzed for nine MMPs single nucleotide polymorphisms (SNPs) using real time polymerase chain reaction TaqMan assays. RESULTS: There were no significant differences in the allele and/or genotype frequencies of all the studied MMPs SNPs among children with dental caries in primary/permanent dentition and the healthy controls (P > 0.05). In addition, similar allele or genotype frequencies of the studied MMPs SNPs were found in children with severe dental caries in their permanent teeth (children with DMFT ≥ 6) and the healthy controls (DMFT = 0, P > 0.05). CONCLUSIONS: This study demonstrated the lack of association between the selected SNPs in candidate genes of MMPs and the susceptibility to or severity of dental caries in both primary and permanent dentitions in Czech children.
Keywords: alely; Dental Caries; Humans; Case-Control Studies; Genetic predisposition; dítě; Polymorphism; DMF Index; studie případů a kontrol; Oral disease; Child; dentice trvalá; ELSPAC; Caries; Alleles; lidé; předškolní dítě; zubní kaz; Adolescent; Dentition, Permanent; Czech Republic; Association study; Česká republika; Child, Preschool; mladiství